2005
DOI: 10.1523/jneurosci.2139-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Oxidase Inhibition Dramatically Increases the Motivation to Self-Administer Nicotine in Rats

Abstract: Nicotine is the major neuroactive compound of tobacco, which has, by itself, weak reinforcing properties. It is known that levels of the enzymes monoamine oxidase A (MAO-A) and MAO-B are reduced in the platelets and brains of smokers and that substances, other than nicotine, present in tobacco smoke have MAO-inhibitory activities. Here, we report that inhibition of MAO dramatically and specifically increases the motivation to self-administer nicotine in rats. These effects were more prominent in rats selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
122
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 35 publications
8
122
2
Order By: Relevance
“…As these mechanisms would suggest, it has been shown that coadministration of methylphenidate augments nicotineinduced increases in extracellular dopamine content in the NAcc (Gerasimov et al, 2000a, b), suggesting that the interactive effects of these drugs on mesolimbic dopamine transmission underlies the behavioral interactions noted in the present study. Regarding self-administration specifically, blockade of central dopamine receptors reduces nicotine self-administration (Corrigall and Coen, 1991;Corrigall et al, 1992), whereas administration of monoamine oxidase inhibitors or the dopamine reuptake inhibitor bupropion increases nicotine self-administration (Guillem et al, 2005(Guillem et al, , 2006Rauhut et al, 2003). One caveat to this interpretation is that methylphenidate and bupropion are relatively nonselective inhibitors of the norepinephrine and dopamine transporters Han and Gu, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As these mechanisms would suggest, it has been shown that coadministration of methylphenidate augments nicotineinduced increases in extracellular dopamine content in the NAcc (Gerasimov et al, 2000a, b), suggesting that the interactive effects of these drugs on mesolimbic dopamine transmission underlies the behavioral interactions noted in the present study. Regarding self-administration specifically, blockade of central dopamine receptors reduces nicotine self-administration (Corrigall and Coen, 1991;Corrigall et al, 1992), whereas administration of monoamine oxidase inhibitors or the dopamine reuptake inhibitor bupropion increases nicotine self-administration (Guillem et al, 2005(Guillem et al, , 2006Rauhut et al, 2003). One caveat to this interpretation is that methylphenidate and bupropion are relatively nonselective inhibitors of the norepinephrine and dopamine transporters Han and Gu, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In a microdialysis study using rats, coadministration of cocaine with nicotine was shown to produce an additive increase in extracellular dopamine levels in the nucleus accumbens (NAcc) relative to administration of nicotine alone (Gerasimov et al, 2000a, b). Similarly, behavioral studies have shown that administration of indirect dopamine agonists, such as monoamine oxidase inhibitors (which prevent intracellular metabolism of dopamine) or bupropion (a dopamine reuptake inhibitor), increase nicotine self-administration in rats (Guillem et al, 2005(Guillem et al, , 2006Rauhut et al, 2003). Thus, it is possible that stimulant drugs increase nicotine self-administration, at least in part, by augmenting nicotine-induced increases in extracellular dopamine levels in the NAcc.…”
Section: Introductionmentioning
confidence: 99%
“…MAO inhibition has been shown to increase nicotine self-administration on fixed-ratio (FR) and progressive-ratio schedules (Guillem et al, 2005;Smith et al, 2015;Villegier et al, 2007). However, the high doses of TCP used by some researchers have been shown to increase nicotine self-administration through acute, off-target effects (eg, monoamine release) rather than the long-lasting effect of MAO inhibition (Lotfipour et al, 2011;Villegier et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although MAO inhibition clearly increases the primary reinforcing effect of nicotine under some conditions (Guillem et al, 2005;Smith et al, 2015), more research is needed. First, the impact of MAO inhibition across different nicotine doses is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, part of the motivation for this study was a resolution of the paradoxical finding that nicotine alone displays very little in the way of 1 st phase reinforcement effect and yet is one of the most commonly abused substances in the world. While a portion of this paradox may be explained by the enhancement of nicotine's 1st phasereinforcement value with the addition of monoamineoxidase-inhibitors and other chemicals commonly found in cigarette smoke [41][42][43][44][45][46] it seems likely that such effects require previous experience with nicotine [47,48]. However, when our analysis focused on nicotine, and food, highresponders, Redish's (2004) hypothesis was robustly supported with significant learning shown for a 2 nd phase CS among blocked nicotine-rewarded animals but not foodrewarded animals and no evidence of blocking using repeated-measures analysis.…”
Section: The Absence Of Blocking Innicotine High-responders As a Possmentioning
confidence: 99%